Drug susceptibility, Prevalence and effect of Pseudomonas aeruginosa on wound healing from burn patients - Azam, Saima; Mustafa, Mohammad Zahid; Taj, Muhammad Kamran; Mengal, Muhammad Azam; Mengal, Muhammad Alam; Hussain, Ashiq (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the prevalence, antibiotic susceptibility and effect of Pseudomonas aeruginosa in relation to burn patients. Method: The cross-sectional study was conducted at the Centre for Advanced Studies in Vaccinology and Biotechnology, University of Balochistan, Quetta, Pakistan, from March 2018 to May 2021, and comprised pus swab cultures were isolated from inpatients with 2nd and 3rd degree burns aged up to 60 years at Bolan Medical Complex Hospital and Sandeman Provinical Hospital, the two main government tertiary care hospitals in Quetta. The samples were immediately cultured, and evaluated using biochemical tests, antibiotic susceptibility and molecular identification using polymerase chain reaction. Data was analysed using SPSS 20. Results: Of the 720 burn wound samples, 424(58.9%) were positive for Pseudomonas aeruginosa; 304(42%) males and 120(16%) females (p<0.02). The overall mean age of the patients was 27.7±6.2 years (range: 1-60 years). The mean total burn surface area was not significantly different in positive 29.6±6.2% and negative 30.3±6.2% cases (p>0.05). The time leading to skin grafts in positive patients was 29.5±6.5 days compared to 22.3±6.3 days for negative patients (p< 0.007), and the time required for wound healing was 25.0±4.7 days and 16.7±5.2 days, respectively (p<0.001). Length of hospital stay of Pseudomonas aeruginosa positive patients was 38.0±7.8 days compared to 32.1±6.8 days for negative patients (p<0.001). Conclusion: Nosocomial infections and multidrug resistance species were observed frequently at the burn wound site. P. aeruginosa. Key Words: Antibiotics, antimicrobial resistance, burn wounds, nosocomial infection, Pseudomonas aeruginosa.